Endgame, 1945 the missing final chapter of World War II - Stafford, David (Little, Brown and Company, 2007)
To end a history of World War II at VE Day is to leave the tale half told. While the war may have seemed all but over by Hitler's final birthday (April 20), Stafford's chronicle of the three months that followed tells a different, and much richer, story.